2008
DOI: 10.1086/588799
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional Magnetohydrodynamic Wave Behavior in Active Regions: Individual Loop Density Structure

Abstract: We present the numerical results from a three-dimensional (3D) nonlinear MHD simulation of wave activity in an idealized active region in which individual, realistic loop density structure is included. The active region is modeled by an initially force-free, dipole magnetic configuration with gravitationally stratified density and contains a loop with a higher density than its surroundings. This study represents an extension to the model of Ofman & Thompson. As found in their work, we see that fast wave propag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 72 publications
(99 reference statements)
5
51
0
Order By: Relevance
“…In fact, Selwa et al (2006Selwa et al ( , 2007a as well as point out that (in 2D) the leakage is "too efficient" to explain the observed damping rates. Analysing 3D numerical simulations of coronal loop oscillations in a magnetic dipole, McLaughlin & Ofman (2008) also find very rapid damping, which (using a comparison with a straight cylinder) they attribute to the loop curvature. However, due to the aspect ratio of our loop (a relatively "fat" loop with a/L ≈ 0.035) the effect of curvature is probably stronger than it would be in realistic coronal loops.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In fact, Selwa et al (2006Selwa et al ( , 2007a as well as point out that (in 2D) the leakage is "too efficient" to explain the observed damping rates. Analysing 3D numerical simulations of coronal loop oscillations in a magnetic dipole, McLaughlin & Ofman (2008) also find very rapid damping, which (using a comparison with a straight cylinder) they attribute to the loop curvature. However, due to the aspect ratio of our loop (a relatively "fat" loop with a/L ≈ 0.035) the effect of curvature is probably stronger than it would be in realistic coronal loops.…”
Section: Discussionmentioning
confidence: 86%
“…8c (curved loop) and Fig. 9c (straight loop) of McLaughlin & Ofman (2008), this scaling also seems to be present (although it was not investigated in detail by these authors). This strong modification of the period due to the curvature appears to contradict the result of Van Doorsselaere et al (2004), who found that the periods of oscillations were only marginally affected by the curvature.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Separately, significant work has gone into modelling coronal waves in active regions to improve understanding of observed coronal oscillations (e.g. Ofman & Thompson 2002;Terradas & Ofman 2004;Brady & Arber 2005;Ofman 2005Ofman , 2007Díaz et al 2006;Verwichte et al 2006;McLaughlin & Hood 2006;McLaughlin & Ofman 2008;Pascoe et al 2009;Schmidt & Ofman 2010), but little attention has been given to focused transport as relevant to flares. This paper seeks to bridge the gap between the sub-disciplines of flare physics and MHD waves by investigating whether, and under what conditions, MHD waves can deliver spatially localised energy fluxes to the chromosphere, and by highlighting for the flare community the wave concepts applicable to this problem.…”
Section: Introductionmentioning
confidence: 99%
“…The observed post-flare kink waves in coronal loops have two main defining characteristics; firstly, they are standing modes, and secondly, they are strongly damped oscillations (in about 1−4 periods, see e.g., Aschwanden et al 2003). Initially there were several physical mechanisms proposed to explain the observed damping, e.g., footpoint leakage (Berghmans & de Bruyne 1995;De Pontieu et al 2001), lateral wave leakage (Smith et al 1997;Brady & Arber 2005;Verwichte et al 2006;Selwa et al 2005Selwa et al , 2007McLaughlin & Ofman 2008), phase mixing (Heyvaerts & Priest 1983;Roberts 2002;Ofman & Aschwanden 2002), resonant absorption (Ruderman & Roberts 2002;Goossens et al 2002), and more recently loop cooling (Morton & Erdélyi 2009). Thus far, resonant absorption, caused by plasma inhomogeneity in the direction transverse to the magnetic field (see Ionson 1978;Hollweg & Yang 1988;Steinolfson & Davila 1993;Ofman & Davila 1995), has proved the most likely candidate for explaining the observed short damping times in coronal loops (see Goossens 2008, for review).…”
Section: Introductionmentioning
confidence: 99%